Assessing the Impact of Industrial Areas on Rural Development (Case Study of Kheirabad Village of Markazi Province) - masoudeh nikooie fard (پژوهش‌های برنامه و توسعه)
Industrialization as one of the rural development approaches can be divided into two groups. The first group are industries that are related to and complementary to the social, economic, and environmental activities of the village and can have positive effects on rural communities. The second category is not related to rural space and usually substitutes for rural economic activities. Rural industrial areas, according to their characteristics, fall into the second category, which is also the dominant approach of our country planners and so far this approach has been used frequently. The assumption of the present paper is that such areas can have harmful effects while not performing well. The purpose of the present study is to investigate the impact of industrial areas on rural development (Case Study: Kheirabad Village of Markazi Province). To this end, the impact of the industrial zone on the village of Kheirabad in Arak city has been evaluated. The evaluation method of this study was questionnaire-based analysis using Mann-Whitney comparative method and factor analysis. The results show that the effect of industrialization on economic, social and infrastructural dimensions is positive and on cultural, agricultural, tourism, environmental and physical dimensions is negative.